PENGARUH RASIO KEUANGAN, PERTUMBUHAN PENJUALAN DAN DIVIDEN TERHADAP HARGA SAHAM - TITA DEITIANA (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2011)
Investor’s need some information to help making appropriate investment decision. This research is aimed to know the influence of financial performance to management decision in paying dividend to the stock holder. The ratio is used for research liquidity, profitability, sales growth and dividend the implication on the stock price. The research showed the company fundamental; its financial aspect became consideration and implication at stock prices. This research use regression linier methods to analyze the influence of profitability, likuidity, sales growth and dividend on stock price in Indonesia Stock Exchange during 4 years continuously start at the year 2004 until 2008. The results show that profitability has affected stock return. While, liquidity, growth and dividen have no affected the stock price.